2021
DOI: 10.1155/2021/6697476
|View full text |Cite
|
Sign up to set email alerts
|

RBM23 Drives Hepatocellular Carcinoma by Activating NF-κB Signaling Pathway

Abstract: Purpose. Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death worldwide, and angiogenesis has been proven to be significantly involved in its progression. However, the molecular mechanism underlying HCC angiogenesis has not been well researched. In this study, RNA Binding Motif Protein 23 (RBM23) was identified as a novel proangiogenic factor in HCC cell lines and tissues. Materials and Methods. Firstly, we analyzed the correlation of clinical specimens. In HCC tissues, the levels of RBM23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous reports have described several functions for RBM23, including the regulation of HCC behaviors and autism neuronal conduction disorders. Han et al 28 revealed that RBM23 promotes the angiogenesis properties of HCC via the NF-κB signaling pathway. Thus, the function of RBM23 in normal hepatocytes and HCC cells may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described several functions for RBM23, including the regulation of HCC behaviors and autism neuronal conduction disorders. Han et al 28 revealed that RBM23 promotes the angiogenesis properties of HCC via the NF-κB signaling pathway. Thus, the function of RBM23 in normal hepatocytes and HCC cells may differ.…”
Section: Discussionmentioning
confidence: 99%
“…The HCC cell line and normal liver cell lines (Lo2) were purchased from Shanghai Fuheng Technology Co., Ltd. and cultured in the corresponding medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin (Invitrogen). Incubation and passaging were performed according to standard protocols in a humidified atmosphere containing 5% CO 2 at 37°C ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Its role is particularly important in lung cancer's onset and progression. Study underscores its significant influence on lung cancer cell proliferation, metastasis, immune response evasion, and targeted treatments [10]. Within the tumor microenvironment, certain, including chronic inflammation, viral infection, and specific drugs, can stimulate and activate the NF-κB pathway, further leading to the progression and metastasis of lung cancer [11].…”
Section: Introductionmentioning
confidence: 99%